KONTEKS GLASS CEILING: KAPABILITAS, REKRUITMEN, DAN REPRESENTASI WANITA (MEN AND WOMEN: WHAT’S THE DIFFERENCES?) - Sari Laelatul Qodriah; Irena Tiara Kusuma (Value : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to obtain empirical evidence whether or not the influence of capability and recruitment to woman representation. This research using correlational quantitative method and data processing assisted with SPSS 20. Population of this research are 6 political parties that exist in Cirebon Regency. The results of this study indicated that only variable capability has a positive and significant influence on the woman representation and has a correlation between variables in the medium category. While the recruitment variable has a correlational between the variables in the low category and it is not significant. Keyword: Capability, Recruitment, Woman Representation, Political Party